Programa Ensino Integral (PEI) e atuação docente em escolas de Educação Básica do município de Guarulhos/SP - Frutuoso, Renato Alves (2023)
In 2012, the Department of Education of the State of São Paulo began implementing the Integral Education Program (IEP), advancing towards the consolidation of universal access to basic education, as well as towards improving the quality of education, seeking to provide training full of students. In the midst of this implementation, the concept of Integral Education was attributed to the Program without an adequate analysis of the characteristics that constitute it. Indifferent to this, the increase in the school day and the integration of the common curriculum base into a diversified knowledge base directly affected both teachers and students, mainly from 2020 onwards, when the state government began an accelerated expansion of accredited schools in this model. The challenges of the entire school community from the perspective of assimilating the principles and assumptions of the IEP are diverse, especially the unrestricted applicability of these precepts in different socioeconomic scenarios. In view of this, the research has the general objective of analyzing the theoretical conceptions and main experiences of Integral Education in Brazil, characterizing its propositions, its results, considering the possible approximations with the IEP, identifying the teaching practice and its effectiveness regarding the principles and premises of the Program. The methodology used is of a qualitative approach, having as procedures the bibliographical research, the documental analysis and the field research in two schools of different socioeconomic realities, from the vision of the professors that work in them. This study was carried out through semi-structured interviews, with 8 teachers from Elementary School Final Years as subjects, 4 teachers from a school in the central region and 4 teachers from the outskirts of the Municipality of Guarulhos/SP. The theoretical basis of the research is based on the following authors: Arroyo (2017), Charlot (2005), Costa (1991, 2006), Costa e Vieira (2006), Dewey (1971), Freire (1996) Moll et al. (2012); Morin (2010), Paro et al. (1988), Gimeno Sacristán (2013), Saviani (2007, 2019) and Teixeira (1967a, 1967b). Among the results of the analyses, about the experience of teachers in the Program's schools, the similarity of the reports in both researched units stands out, both with regard to the difficulties in putting the IEP methodologies into practice, as well as the positive points of the Program in relation to partial schools. With regard to attributing the concept of Integral Education to schools accredited to the IEP, it was found that there is no alignment between the Program's conceptions with the concept of Integral Education, in light of the references on which the research is based